Тяжелые металлы в донных отложениях Севастопольской бухты - Кадошников, В.М.; Шкапенко, В.В.; Горлицкий, Б.А.; Писанская, И.Р.; Смирнова, Ю.Д. (Мінералогічний журнал, 2011)
Рассмотрена природа органических и минеральных веществ в донных осадках на выходе из Севастопольской бухты. Показано, что минеральный состав донных отложений представлен преимущественно высокодисперсным кальцитом и кварцем, с незначительной примесью глинистых минералов, а органические вещества — гумусом с примесью углеводородов. Донные осадки содержат тяжелые металлы, количество которых зависит от минерального состава и природы органических веществ. Розглянуто природу органічних та мінеральних речовин в донних осадах Севастопольської бухти. Показано, що мінеральний склад донних відкладів представлений переважно високодисперсним кальцитом та кварцом з незначною домішкою глинистих мінералів, а органічні речовини — гумусом з домішкою углеводнів, кількість яких залежить від мінерального складу та природи органічних речовин. Interrelation of bottom sediments contamination with heavy metals and quantity of organic matter is considered in the article. Bottom sediments are represented by high - dispersed calcite and quartz together with admixtures of clay minerals. Organic matter of bottom sediments mainly consists of humic substances, and nonpolar hydrocarbons. It is shown that the contamination level of bottom sediments in the Sevastopol bay is much higher than in the area of the Karadag Nature Reserve. Hydrocarbons content in bottom sediments at the exit from the Sevastopol bay is much less than the total content of organic matter. Main quantity of organic substances in bottom sediments is presented by humus, some part of which is in the form of humic acids. Low content of hydrocarbons in the studied samples is caused by transformation of oil hydrocarbons into humus. The content of copper and zinc is correlated with quantity of humus, and main amounts of these elements are bound in the form of organic complexes. Contamination of sediments by lead and chromium are mainly associated with arrival of these elements with fuel hydrocarbons and are concentrated in the locations of the Navy. High levels of zinc and lead in bottom sediments in the area of ships dislocation is caused by fuel hydrocarbons and zinc-containing antifouling paints. The content of manganese in bottom sediments near the outlet from the Sevastopol bay is small and is comparable with the amount of manganese in bottom sediments of the Karadag Nature Reserve coastal zone. Low content of manganese in bottom sediments near the outlet from the Sevastopol bay is connected with deposition of manganese in bottom sediments and is driven by inner-basin processes. Low manganese content at the outlet of the bay is related to the fact that under certain hydrological situations manganese is removed from the South bay and, while getting into a qualitatively different redox conditions in the outlet part of the bay is transformed into insoluble forms, contributes to increasing of manganese concentrations in the sediments inside the bay.